Effectiveness of Village Fund Utilization in Village Community Empowerment in Tondowolio Village, Tanggetada District, Kolaka Regency - Elmiana Elmiana; Dewi Sulfa Saguni; Mardiana Mardiana; Sudiarti Dewi Kurra (Program Pascasarjana Universitas Negeri Makassar, 2022)
This study aims to determine the effectiveness of the use of village funds in empowering rural communities in Tondowolio Village, Tanggetada District, Kolaka Regency. This study uses a descriptive method using qualitative data types, data collection is carried out through observation, interviews, and documentation, data analysis is carried out by collecting all information, reducing data, data validity and drawing conclusions. The results of the research analysis show that the use of Village Funds for community empowerment is in accordance with its designation but is not yet maximized. It can be seen from the indicators in measuring effectiveness, namely the understanding of the program where the community's understanding is still minimal about village funds. The target of village funds is in accordance with the RKPDes which has been prepared by the village government and village communities, the timeliness is still not optimal because the implementation of village funds is adjusted to the disbursement of village funds. The achievement of the goals has not been fully achieved because the empowerment program is still limited to meeting needs and providing convenience for the community but there is no new economy created that provides a source of income for rural communities. As well as real changes, the existence of this village fund provides a good change for the village community and the village government.